HQSAR study of tricyclic azepine derivatives as an EGFR (Epidermal growth factor receptor) inhibitors - Chung, Hwan Won; Lee, Kyu Whan; Oh, Jung Soo; Cho, Seung Joo (KOREAN SOC TOXICOGENOMICS & TOXICOPROTEOMICS, 2007)
Stimulation of epidermal growth factor receptor (EGFR) is essential in signaling pathway of tumor cells. Thus, EGFR has intensely studied as an anticancer target. We developed hologram quantitative structure activity relationship (HQSAR) models for data set which consists of tricyclic azepine derivatives showing inhibitory activities for EGFR. The optimal HQSAR model was generated with fragment size of 6 to 7 while differentiating fragments having different atom and connectivity. The model showed cross-validated q(2) value of 0.61 and non-cross-validated r(2) value of 0.93. When the model was validated with an external set excluding one outlier, it gave predictive r(2) value of 0.43. The contribution maps generated from this model were used to interpret the atomic contribution of each atom to the overall inhibition activity. This can be used to find more efficient EGFR inhibitors.